Логика: учебник для юридических вузов / В. И. Кириллов, А. А. Старченко - Кириллов Вячеслав Иванович (Institutiones, 1999)
Экземпляры: аб. (2000) / Инвентарный номер: 42307 / Цена: / Сис.шифр: 87.4 / Авт.знак: К 43 / ГРНТИ: 02.21 / ББК: 87.4я73